The Pernicious Consequences Of Political Corruption In Indonesia - Handayani, Febri (Universitas Islam Indonesia, 2019)
Political corruption is an ethical and juridical deviation committed by people with positions of political power. Political corruption has a more structured system than general corruption cases, because political corruption is committed to satisfy the interests of political parties. Political corruption cases are commonplace in a country where political corruption is rampant. This is a normative legal research, using a case approach, conceptual approach, and statutory approach, as well as qualitative analysis. Based on this analysis, it is conclusive that political corruption is an action carried out by political elites or state government officials that has an impact on the country's political and economic situation. People and or parties who have political positions usually commit these acts. Political corruption can be in the form of abuse of authority, granting influence, lobbying, self-enrichment, vote-buying, and election fraud. In terms of effectiveness of the law, the pervasive political corruption in Indonesia is attributed to ineffective law enforcement related to political corruption. In fact, some former corruption convicts may become a corruption recidivist simply because the law enforcement of political corruption fails to have any deterrent effect due to the disharmony between laws and regulations related to political corruption. The rampant political corruption practices result in violations against the principles of good governance.Keywords: Legal consequences, political corruptionKonsekuensi Buruk Korupsi Politik di IndonesiaAbstrakKorupsi politik adalah penyimpangan etika dan juga penyimpangan yuridis yang dilakukan oleh orang-orang yang memiliki posisi dan kekuasaan politik. Korupsi politik memiliki sistem yang lebih terstruktur dibandingkan kasus korupsi umum karena korupsi politik ini dilakukan demi memenuhi kepentingan partai politik. Kasus korupsi politik merupakan hal yang lumrah ditemukan di negara yang korupsi politiknya merajalela. Penelitian ini merupakan penelitian hukum normatif dengan menggunakan pendekatan kasus, konseptual, dan perundang-undangan, serta analisis kualitatif. Berdasarkan analisis tersebut, dapat disimpulkan bahwa korupsi politik adalah tindakan yang dilakukan oleh elit politik atau pejabat pemerintah yang berdampak pada situasi politik dan ekonomi negara. Biasanya orang dan/atau partai yang memiliki jabatan politik yang melakukan perbuatan tersebut. Korupsi politik dapat berupa penyalahgunaan wewenang, pemberian pengaruh, lobi, pengayaan diri, pembelian suara, hingga kecurangan pemilu. Dari sisi efektifitas hukum, maraknya korupsi politik di Indonesia disebabkan oleh tidak efektifnya penegakan hukum terkait korupsi politik. Bahkan, beberapa mantan narapidana korupsi bisa menjadi residivis korupsi hanya karena penegakan hukum korupsi politik tidak memberikan efek jera akibat disharmonisasi antara peraturan perundang-undangan terkait korupsi politik. Maraknya praktik korupsi politik mengakibatkan pelanggaran terhadap prinsip-prinsip tata pemerintahan yang baikKata kunci: Konsekuensi Hukum; Korupsi Politik